From autism to eating disorders and more: the role of oxytocin in neuropsychiatric disorders - Romano, Adele; Tempesta, Bianca; Micioni Di Bonaventura, Maria Vittoria; Gaetani, Silvana (Frontiers in Neuroscience, 2016)
Oxytocin (oxy) is a nonapeptide hormone synthesized in the paraventricular and supraoptic nuclei of the hypothalamus. Like other neuropeptides, oxy action can simultaneously include regionally and temporally varying combinations of neurotransmitter and neuromodulator activities. Additionally, through the neurohypophysis, oxy is secreted into the systemic circulation to act as a hormone, thereby influencing several body functions. Oxy plays a pivotal role in parturition, milk let-down and maternal behavior and has been demonstrated to be important in the formation of pair bonding between mother and infants as well as in mating pairs. Furthermore oxy is increasingly recognized as an important regulator of social behaviors, including social decision-making, evaluation and response to social stimuli, social interactions and social memory processes. Increasing evidences suggest a crucial role played by oxy in the pathophysiology of certain neuropsychiatric disorders such as autism, eating disorders, schizophrenia, mood and anxiety disorders. The potential use of oxy in these mental health disorders is becoming more and more accepted since many positive effects have been attributed to this neuropeptide. This review will provide an overview of the current understanding on the role played by oxy in different physiological functions and complex behaviors, as well as on its role and impact in different psychiatric disorders, to highlight the need of further investigations on this target that might contribute to the development of novel more efficacious therapies.